What is the point of religious education? - Clayton, Matthew; Stevens, David (SAGE Publications, 2018)
Some liberal societies continue to require their schools to offer non-directive, but specifically religious education as part of the curriculum. This paper challenges that practice. It does so by articulating and defending a moral principle, which asserts that education policy must be regulated by principles that are acceptable to reasonable people. Thereafter, we argue that the leading arguments for prioritizing the study of religion in schools—arguments that claim that religion is special or that assert that the majority or parents are morally permitted to prioritise religion in schooling—are incompatible with the acceptability requirement.